An analytical study of the availability of comprehensive knowledge marketing management in Iraqi sports institutions - Luma Samer Hamoodi; Nadeema Badr Mohammed; Zainab Ali Abdul Ameer; Missaa Nadem; Nihad Mohammed Alwan; Najlaa Abbas AL-Zuhairi; Liqaa Abdullah Ali (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Objective: The current study aimed to prepare a measure for comprehensive knowledge marketing management. In the Iraqi sports institutions under study, identifying the extent of each dimension of comprehensive knowledge marketing management.